Regional trends in In-hospital Cardiac Arrest following sepsis-related admissions and subsequent mortality. (October 2019) - Desai, Rupak; Parekh, Tarang; Patel, Upenkumar; Hanna, Bishoy; Damarlapally, Nanush; Patel, Chiranj; Doshi, Rajkumar; Savani, Sejal; Sachdeva, Rajesh; Kumar, Gautam
Abstract: Background: Previous studies have reported regional variation in either the incidence or outcomes of sepsis or In-hospital Cardiac Arrest (IHCA) discretely; however, regional variations in the incidence and outcomes of sepsis-associated IHCA (SA-IHCA) have never been studied. Methods: From the National Inpatient Sample (NIS), discharges with sepsis and sepsis-associated IHCA were identified in 4 geographic regions (Northeast, Midwest, South, West) from 2007 to 2014 using applicable ICD-9-CM codes. We assessed the regional incidence and trends in SA-IHCA and subsequent inpatient outcomes. Results: Out of 8, 058, 091 sepsis-related admissions, 187, 163 (2.3%) were associated with IHCA with a rising trend in the incidence from 2007- to 2014 (2.0% to 2.6%, ptrend  < 0.001). The overall incidence of SA-IHCA was highest in South (2.6%) with the highest mortality in West (74.4%) (p < 0.001). The incidence of SA-IHCA increased in the South (2.4%–3.0%) and Midwest (1.6%–2.4%) from 2007 to 2014. Mortality has not significantly increased or decreased across all regions. Compared with the West, survivors in the Northeast, Midwest, and the South were less likely to be discharged home and were more likely to be transferred to other facilities. In the SA-IHCA cohort, the mean length of stay for SA-IHCA was highest in Northeast (˜10.9 days) and lowest in Midwest (˜8.6 days) (p < 0.001). Hospital charges were highest in the West ($234, 278) and lowest in the Midwest ($125, 725) (p < 0.001). Conclusion: This nationwide analysis demonstrates that the highest incidence of SA-IHCA is in the Southern region of the US whereas the associated in-hospital mortality was highest in the West. The incidence of SA-IHCA is rising in the Midwest and South from 2007 to 2014. Despite significant advances in the treatment of sepsis and IHCA, there has been no significant improvement in the incidence of SA-IHCA and subsequent survival in any US geographic region from 2007 to 2014.